Bioactivity Screening of Extracts from Icelandic Seaweeds for Potential Application in Cosmeceuticals - Sophie Jensen; Júlía Karítas Helgadóttir; Rósa Jónsdóttir (Phycology, 2024)
Seaweed is a great source of biologically active metabolites which could prove interesting in cosmeceutical applications. In this study, seven Icelandic seaweed species (Ascophyllum nodosum, Alaria esculenta, Laminaria hyperborea, Laminaria digitata, Saccharina latissima, Palmaria palmata, and Schizymenia jonssonii) were screened for total polyphenol content, antioxidant properties, and inhibition of skin-degrading enzymes. Antioxidant assays included DPPH (2,2-diphenyl-1-picrylhydrazyl), reducing power, and ORAC (oxygen radical absorbance capacity). In most assays, A. nodosum extracts were the most active. A. nodosum extracts also showed the strongest inhibition of the skin-degrading enzymes elastase and collagenase at low concentrations, demonstrating its skin-protective qualities. To further investigate the activity, A. nodosum was subsequently extracted with solvents with increasing polarity into seven different extracts. Compared to other extracts, the extracts obtained by extraction with acetone and methanol showed the highest activity in all assays. Extracts obtained with room-temperature water and 85 °C water also demonstrated moderate to high activities. The outcomes of this study support the potential utilization of the brown seaweed A. nodosum as a source of natural ingredients in cosmeceuticals.